Clinical Features and Outcome of 79 Dogs With Digital Squamous Cell Carcinoma Undergoing Treatment: A SIONCOV Observational Study - Marconato, Laura; Murgia, Daniela; Finotello, Riccardo; Meier, Valeria; Morello, Emanuela Maria; Pisoni, Luciano; Foglia, Armando; Guerra, Dina; Chalfon, Carmit; Aralla, Marina; Mesto, Paola; Annoni, Maurizio; et al. (Frontiers in Veterinary Science, 2021)
In dogs, digit squamous cell carcinoma (SCC) is uncommon. Clinical signs are frequently underestimated, leading to a diagnostic delay. The purpose of this retrospective study was to report our experience regarding the clinical presentation, diagnostic work-up, treatment and outcome of 79 client-owned dogs with SCC of the digit. The greatest majority (84.8%) of dogs was dark-coated. Schnauzers represented approximately one third of the study population, and had a poorer outcome compared with other breeds. The majority of SCCs occurred in the front limbs (61%), and bone lysis was frequently observed (92.4%). Approximately 9% of dogs had involvement of multiple digits, and this was associated with a shorter time to progression (TTP; P=0.047). Similarly, a duration of clinical signs >90 days was associated with a shorter TTP (P=0.02). Regional lymph node metastases were documented in 17.7% of dogs at admission and were significantly associated with tumor-related death (P<0.001). At presentation, none of the dogs had evidence of distant metastasis. Digit amputation achieved adequate local tumor control in the majority of cases. Adjuvant chemotherapy and radiation therapy were carried out in 21.5% of cases, with uncertain benefit. Due to the relatively non-aggressive clinical behavior of digit SCC, chemotherapy should only be offered in the case of metastatic disease. Approximately one fourth of dogs developed de novo SCCs during the follow-up. Careful examination of the digits should be encouraged in breeds considered at high risk and in dogs with a previous history of digital SCC.